Pengaruh Cara Pengeringan Simplisia Daun Senggani (Melastoma malabathricum L.) Terhadap Aktivitas Antioksidan Menggunakan Metode DPPH (2,2-difenil-1-pikrilhidrazil) - Luliana, Sri; Purwanti, Nera Umilia; Manihuruk, Kris Natalia (UI Scholars Hub, 2016)
Drying is the most important step to keep the compound stability in simplicia. The objective of this research is to know the effect of drying methods on antioxidant activity in Melastoma malabathricum L. The drying methods tested were oven-drying at 40°C, direct sunlight, indirect sunlight, air-drying at ± 25°C and fresh samples as control. Result revealed that the drying methods of simplicia were significant differences for antioxidant activity in Melastoma malabathricum L. (p < 0,05). Drying method that has the highest antioxidant activity was by air-drying at ± 25°C is 54.60 %.